A Houttuynia cordata–based Chinese herbal formula improved symptoms of allergic rhinitis during the COVID-19 pandemic. Issue 6 (14th April 2022) - Chang, Kai-Wei; Lin, Tung-Yi; Fu, Shu-Ling; Ping, Yueh-Hsin; Chen, Fang-pey; Kung, Yen-Ying
Abstract : Background: The symptoms of coronavirus disease 2019 (COVID-19) such as hyposmia, rhinorrhea, nasal obstruction, and cough are similar to those of chronic allergic rhinitis (AR). Such symptoms can easily lead AR patients to unnecessary anxiety, misdiagnosis, and invasive diagnostic tests in the COVID-19 pandemic. Interleukin-6 (IL-6) is an important mediator for chronic AR and plays a crucial role in the inflammation of COVID-19. Houttuynia cordata (HC) has been shown to reduce nasal congestion and swelling by suppressing the activation of IL-6 and is used to fight COVID-19. A novel HC-based Chinese herbal formula, Zheng-Yi-Fang (ZYF), was developed to test effects on nasal symptoms of patients with AR in the COVID-19 pandemic. Methods: Participants aged between 20 and 60 years with at least a 2-year history of moderate to severe perennial AR were enrolled. Eligible participants were randomly allocated to either the intervention group (taking ZYF) or the control group (using regular western medicine) for 4 weeks. The Chinese version of the Rhinosinusitis Outcome Measures was used to evaluate impacts on quality of life and nasal symptoms of participants with AR. In addition, the effect of ZYF on lipopolysaccharide (LPS)-induced IL-6 was investigated. Results: Participants with AR taking ZYF improved their symptoms of nasal obstruction, nasal secretion, hyposmia, and postnasal drip in comparison with those of the control group. Meanwhile, ZYF exhibited inhibition of IL-6 secretion in the LPS-induced inflammatory model. Conclusion: ZYF has potential effects to relieve nasal symptoms for AR during the COVID-19 pandemic.